2020
DOI: 10.1108/ijsms-04-2020-0053
|View full text |Cite
|
Sign up to set email alerts
|

Beyond “who pays?”: stadium development and urban governance

Abstract: PurposeThe purpose of this paper is to reframe analyses of stadium and arena subsidization policies from perspectives centered upon economic and financial issues toward a perspective focused on broader issues of urban governance and the public purposes of sports facilities. Such assessments would provide a better understanding of whether such use of public resources represents good public policy.Design/methodology/approachTo demonstrate this, the paper uses an integrated literature review to offer a historical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 37 publications
0
2
0
Order By: Relevance
“…Literature [11] aimed to explore how community sports programs can be effective in health promotion by following up and pointing out that the health-promoting effects of community sport on socially disadvantaged groups come from the process of peer-to-peer experiential learning, increased responsibility taking, and reflexivity. Literature [12] analyzes and evaluates the development of urban sports facilities based on an urban governance-driven perspective to maximize public benefits among a wide range of people. Literature [13] studied the social benefits and impacts of surfing programs in New Zealand and found that there are two views on surfing, one pointing out that surfing heals and helps people with self-management and self-improvement, and the other viewpoint that surfing advocates freedom and is not conducive to the stability of social order.…”
Section: Introductionmentioning
confidence: 99%
“…Literature [11] aimed to explore how community sports programs can be effective in health promotion by following up and pointing out that the health-promoting effects of community sport on socially disadvantaged groups come from the process of peer-to-peer experiential learning, increased responsibility taking, and reflexivity. Literature [12] analyzes and evaluates the development of urban sports facilities based on an urban governance-driven perspective to maximize public benefits among a wide range of people. Literature [13] studied the social benefits and impacts of surfing programs in New Zealand and found that there are two views on surfing, one pointing out that surfing heals and helps people with self-management and self-improvement, and the other viewpoint that surfing advocates freedom and is not conducive to the stability of social order.…”
Section: Introductionmentioning
confidence: 99%
“…Leisure research focuses on public entertainment and park management, highlighting the government's public service function with a welfarism orientation, while tourism research tends to have a commercial orientation [11]. Research on urban leisure space mainly focuses on a particular type of public urban leisure space, such as parks [16], green spaces [17], sports and recreation sites [18], cultural venues [19], and coastal areas [20]. Most of the literature focuses on the planning and management of urban leisure space [21], public access to recreational spaces [22], health perceptions [23], and service experiences [24].…”
Section: Introductionmentioning
confidence: 99%